EXTENSIVE FASCIOTOMY AND ESCHAROTOMY WOUND ARTEFACTS AT MEDICO LEGAL AUTOPSY: TWO CASE REPORTS - Venkatesh, J; Sharma, Munish; Behera, Chittaranjan (Journal of Forensic Medicine and Toxicology, 2024)
Therapeutic artefacts are commonlyobserved at routine autopsy by the forensic pathologist. It is mostlyproduced during resuscitation and medical intervention. We report two unusual therapeutic artefacts cases i.e. extensive fasciotomy and escharotomy wound artefacts at medico legal autopsy. Extensive fasciotomy was done as a therapeutic measure for compartment syndrome in Therapeutic artefacts;Extensive fasciotomy; 1 The deceased’s relatives are more artefacts. Some of the few artefacts resemble actual pathological or physiological features that could be very difficult to differentiate for even experienced forensic pathologists.2 We are reporting cases of therapeutic artefact due to fasciotomy and escharotomy wounds at autopsy,
Keywords: artefacts; disease; underwent